Comparison of routine and automated office blood pressure measurement. Issue 4 (August 2019) - Cheng, Robin Z.; Bhalla, Vivek; Chang, Tara I.
Abstract : Objectives: From April to October 2018, we implemented a blood pressure measurement quality improvement project at our Hypertension Center. We aimed to compare blood pressure measured using routine, non-standardized office blood pressure and Systolic Blood Pressure Intervention Trial-like automated office blood pressure protocols. Methods: In 202 consecutive patients, we measured blood pressure using routine clinic methods and an automated office blood pressure protocol (5 min of rest followed by three blood pressure measurements at 1-min intervals). Results: The mean routine blood pressure was 145.6/76.4 mmHg and the mean automated office blood pressure was 135.3/70.1 mmHg. The mean paired difference in blood pressure was 10.3/6.3 mmHg, and Bland-Altman plots demonstrated wide limits of agreement. Using the systolic blood pressure goal of 130 mmHg, 26.9% of the patients not at goal by routine blood pressure were at goal by automated office blood pressure. Conclusions: Misclassifications of patient blood pressure control status and the wide variability between routine blood pressure and automated office blood pressure support the wider clinical implementation of automated office blood pressure to improve standardization, minimize incorrect blood pressure measurement and avoid over-treatment. Abstract : Supplemental Digital Content is available in the text.